2000
DOI: 10.1104/pp.123.3.959
|View full text |Cite
|
Sign up to set email alerts
|

Compression Wood-Responsive Proteins in Developing Xylem of Maritime Pine (Pinus pinasterAit.),

Abstract: When a conifer shoot is displaced from its vertical position, compression wood (CW) is formed on the under side and can eventually return the shoot to its original position. Changes in cell wall structure and chemistry associated with CW are likely to result from differential gene/protein expression. Two-dimensional polyacrylamide gel electrophoresis of differentiating xylem proteins was combined with the physical characterization of wooden samples to identify and characterize CW-responsive proteins. Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 65 publications
4
77
0
1
Order By: Relevance
“…ACC oxidase protein accumulated significantly more in secondary xylem compared to needles and in response to gravitational stress in P. pinaster Ait. (Plomion et al 2000). The SNP (PGWD1-0560) represents a nonsynonymous substitution (GGG-GAG) coding for glycine and glutamine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ACC oxidase protein accumulated significantly more in secondary xylem compared to needles and in response to gravitational stress in P. pinaster Ait. (Plomion et al 2000). The SNP (PGWD1-0560) represents a nonsynonymous substitution (GGG-GAG) coding for glycine and glutamine.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 747 candidate genes were identified for SNP discovery and classified on the basis of expression data or information available for each gene. The expression data included an analysis of vascular tissues and needles in P. glauca with a custom cDNA array based on 9503 gene clusters (Pavy et al 2008a) and three such studies of secondary xylem carried out in pine species (Plomion et al 2000;Pavy et al 2005b;Paiva 2006). The functional annotations considered white spruce transcription factors, as well as sequences known to be involved in cell wall and lignin synthesis, as well as sequences reported to be potentially involved in wood formation.…”
Section: Association Populationmentioning
confidence: 99%
“…In hybrid aspen (Populus tremula 3 Populus tremuloides), overexpression of certain ERFs affects cambial growth and wood chemistry (lignin and carbohydrate content; Vahala et al, 2013). During compression wood formation in maritime pine (Pinus pinaster), the ethyleneforming enzyme 1-aminocyclopropane-1-carboxylate oxidase accumulates strongly (Plomion et al, 2000). In addition to eccentric growth, compression wood of conifers contains higher levels of lignin compared with normal vertical wood.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…SAMS has been identified in the xylem of Pinus pinaster (Plomion et al, 2000) and characterized in rice (Breusegem et al, 1994), Populus (Vander Mijnsbrugge et al, 2000) and other organisms. This enzyme is a universal donor of the methyl group in several transmethylation reactions, which involve many types of acceptor molecules (Plomion et al, 2000). SAMS initiates the methylation of the precursor of monolignols during the biosynthesis of lignin (Ye et al, 1994), where it has also been identified in the response to salt stress in tomato plants.…”
Section: Proteomic Characterization Of Eucalyptus Clonesmentioning
confidence: 99%
“…Proteomic analysis has become a timely tool in the functional characterization of trees and, along with analysis of transcripts, has been increasingly used in the study of plants (Rengel et al, 2009). The analysis of protein profiling in two-dimensional (2-D) gels is important for two reasons: i) the determination of proteins relate directly to the functional mechanisms, while the determination of transcripts is by definition indirectly linked to cellular functions, and ii) recent findings have pointed out that the abundance of protein can hardly be predicted from the abundance of corresponding mRNA transcripts (Plomion et al, 2000). In this context, it is worth recalling that proteins are responsible for the final phenotype of the cell, i.e., the final product of gene expression after undergoing several posttranslational modifications, such as the removal of signal peptide, phosphorylation and glycosylation.…”
Section: Introductionmentioning
confidence: 99%